2007
DOI: 10.2165/00003495-200767070-00007
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Hypotension

Abstract: For half a century, controlled hypotension has been used to reduce bleeding and the need for blood transfusions, and provide a satisfactory bloodless surgical field. It has been indicated in oromaxillofacial surgery (mandibular osteotomy, facial repair), endoscopic sinus or middle ear microsurgery, spinal surgery and other neurosurgery (aneurysm), major orthopaedic surgery (hip or knee replacement, spinal), prostatectomy, cardiovascular surgery and liver transplant surgery. Controlled hypotension is defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
132
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(135 citation statements)
references
References 144 publications
1
132
1
1
Order By: Relevance
“…However, hypotensive agents have several disadvantages, such as reflex tachycardia and tachyphylaxis [9] . Therefore, it is necessary to use compounds with dose-response effects that are predictable [11] . In recent years, remifentanil as a short acting opioid receptor agonist has been used for this purpose in order for a mild to moderate reduction of blood pressure and as an effective agent for controlled hypotension [12] .…”
Section: Introductionmentioning
confidence: 99%
“…However, hypotensive agents have several disadvantages, such as reflex tachycardia and tachyphylaxis [9] . Therefore, it is necessary to use compounds with dose-response effects that are predictable [11] . In recent years, remifentanil as a short acting opioid receptor agonist has been used for this purpose in order for a mild to moderate reduction of blood pressure and as an effective agent for controlled hypotension [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 shows the respondents' drug choices in blood pressure control, as well as their first line of choices. Blood pressure targets in controlled hypotension should always be tailored to the individual patient's co-morbidities 3,4 . Given that the questionnaire lacks an individualised clinical context, it is unsurprising that nearly half of the respondents aimed for MAP of 20-30% below baseline.…”
Section: Drug Choices For Ess and Controlled Hypotensionmentioning
confidence: 99%
“…While intra-operative esmolol has been established as an agent that can lower heart rate and blood pressure, and improve surgical conditions 1,3,4,22 , there are two studies which explored pre-operative oral beta-blockers for ESS and found good efficacy in improving operative conditions 5,25 . However, as expected from drug elimination, the studies Proceedings of Singapore Healthcare  Volume 23  Number 4  2014 also showed better operative conditions earlier compared to the end of surgery 5 .…”
Section: Anti-hypertensive Agentsmentioning
confidence: 99%
“…[1] It is indicated in endoscopic sinus or middle ear microsurgery, oromaxillofacial surgery, neurosurgery, major orthopaedic surgery, prostatectomy, cardiovascular and liver transplant surgery.…”
Section: Introductionmentioning
confidence: 99%